Peran Kelembagaan Dalam Pengelolaan Persampahan Di Kabupaten Trenggalek - Puspasari, Gandhi Rahma; Mussadun, Mussadun (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
One of the social problems that often arise in urban areas is a waste problem. Waste problem is basically caused by many things, such as the lack of good waste management, the behavior of a society that is still low in maintaining hygiene and environmental health, as well as the growing population, thus adding of waste produced by households. Waste management in the region, will involve communities, government, NGOs and the private sector. But in Trenggalek, the absence of private parties who participated in addressing rural waste. Waste management in Trenggalek handled by the government and the people who lead the waste pelayananaan less than optimal or not in accordance with existing regulations. The aim of this study was to assess the extent to which institutional role in waste management in Trenggalek, in creating a healthy environment, berhindar of soil and water pollution caused by garbage. The analysis in this study was performed using Pearson correlation analysis, crosstab analysis and scale analysis. Results from this study were 1) Waste in Trenggalek differentiate into 2 (two), namely organic and inorganic waste, the most dominant is the leaf litter and food waste amounted to 81.30%. 2) Institute for waste management there are only two (2) institutions, namely the government and society. 3) Waste management in Trenggalek done by way of being transported by a janitor, burned and dumped into the river. 4) The role of each institution shows that government plays an important role in waste management in Trenggalek. 5) Based on the analysis of the correlation between institutional waste management indicates that the government has a weak relationship with the community, so that waste management is less than optimal.